Glomerular filtration rate in cows estimated by a prediction formula. (3rd September 2014) - Murayama, Isao; Miyano, Anna; Sato, Tsubasa; Iwama, Ryosuke; Satoh, Hiroshi; Ichijyo, Toshihiro; Sato, Shigeru; Furuhama, Kazuhisa
Abstract To testify the relevance of Jacobsson's equation for estimating bovine glomerular filtration rate (GFR), we prepared an integrated formula based on its equation using clinically healthy dairy (n = 99) and beef (n = 63) cows, and cows with reduced renal function (n = 15). The isotonic, nonionic, contrast medium iodixanol was utilized as a test tracer. The GFR values estimated from the integrated formula were well consistent with those from the standard multisample method in each cow strain, and the Holstein equation prepared by a single blood sample in Holstein dairy cows. The basal reference GFR value in healthy dairy cows was significantly higher than that in healthy beef cows, presumably due to a breed difference or physiological state difference. It is concluded that the validity for the application of Jacobsson's equation to estimate bovine GFR is proven and it can be used in bovine practices.